Kapasitas Inovasi Program Dana Pembangunan Wilayah Kelurahan dalam Mendukung Percepatan dan Pemerataan Pembangunan Daerah - Khaerunissa, Siti; Hasanah, Budi; Sururi, Ahmad (Dialogue : Jurnal Ilmu Administrasi Publik, 2023)
The Subdistrict Regional Development Fund Program (DPWK) is an innovation from the Cilegon Municipality Government which aims to improve the administrative function of subdistrict government in providing services to the community, encourage accelerated and equitable regional development and encourage the acceleration of regional poverty reduction. The aim of this research is to determine the innovation capacity of the Village Regional Development Fund Program (DPWK) in supporting accelerated and equitable development in Cilegon Municipality. This research method uses a descriptive method with a qualitative approach. Data collection was carried out through interviews, observation and documentation. The research results show that the Subdistrict Regional Development Fund Program has been running well, although there are still several problems such as limited community empowerment programs and only prioritizing regional infrastructure development programs and the low collaborative capacity of program implementers. Because the Cilegon Municipality government is paying more attention to community empowerment programs, intensive communication with the implementers of the Village Regional Development Fund (DPWK) program in Cilegon Municipality in creating ideal collaboration and prioritizing regional infrastructure development programs